Transcriptionally Active Human Papillomavirus in Male Genital Lichen Sclerosus, Penile Intraepithelial Neoplasia, and Penile Squamous Cell Carcinoma - Georgios Kravvas; Boyu Xie; Aiman Haider; Michael Millar; Hussain M Alnajjar; Alex Freeman; Asif Muneer; Christopher B Bunker; Aamir Ahmed (JID Innovations)
Penile intraepithelial neoplasia (PeIN) and penile squamous cell carcinoma (PeSCC) are both thought to be associated with male genital lichen sclerosus and human papillomavirus (HPV) infection through dichotomous pathways: (i) undifferentiated PeIN and warty/basaloid PeSCC are thought to be HPV related, whereas (ii) differentiated PeIN and usual PeSCC are considered HPV independent. Tissue arrays were constructed from male genital lichen sclerosus, undifferentiated and differentiated PeIN, usual-type PeSCC, and unaffected tissues. Staining for p16 and for high-risk and low-risk HPV subtypes through RNAscope was performed. The expression of HPV RNA and p16 were quantified, and appropriate statistical comparisons were undertaken. High-risk HPV was prevalent in undifferentiated PeIN (77%) and less so in PeSCC (46%) and was exiguous or absent in all other tissues. LR HPV was only observed in 2 tissue cores. Strong p16 staining exhibited 96.15% sensitivity and 100% specificity for high-risk HPV. Transcriptionally active HPV is unlikely to be implicated in male genital lichen sclerosus and differentiated PeIN, although it is clearly important in undifferentiated PeIN. The high prevalence of high-risk HPV in usual PeSCC challenges the existing paradigm. Strong p16 positivity was a reliable surrogate marker for the detection of transcriptionally active high-risk HPV.